2023
DOI: 10.1021/jacs.3c05178
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Coupling Control in Triangulene Dimers

Hongde Yu,
Thomas Heine

Abstract: Metal-free magnetism remains an enigmatic field, offering prospects for unconventional magnetic and electronic devices. In the pursuit of such magnetism, triangulenes, endowed with inherent spin polarization, are promising candidates to serve as monomers to construct extended structures. However, controlling and enhancing the magnetic interactions between the monomers persist as a significant challenge in molecular spintronics, as so far only weak antiferromagnetic coupling through the linkage has been realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Consequently, we proceed to compute the J values of the supercell junction model shown in Figure (b), which explicitly includes the electrodes. Intriguingly, the PBE functional yields an appreciably positive J at θ = 0, contradicting the Goodenough–Kanamori rule, ,, which typically predicts a negative J at small θ values. To address this discrepancy, we employ the strongly constrained and appropriately normed (SCAN) meta-GGA functional to determine the total energy and the spin coupling between the two radicals within the Au/ 2-OS /Au junction.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Consequently, we proceed to compute the J values of the supercell junction model shown in Figure (b), which explicitly includes the electrodes. Intriguingly, the PBE functional yields an appreciably positive J at θ = 0, contradicting the Goodenough–Kanamori rule, ,, which typically predicts a negative J at small θ values. To address this discrepancy, we employ the strongly constrained and appropriately normed (SCAN) meta-GGA functional to determine the total energy and the spin coupling between the two radicals within the Au/ 2-OS /Au junction.…”
mentioning
confidence: 80%
“…Research on intramolecular electron magnetic interactions is essential in both fundamental science and applied technologies. , Recent efforts have focused on providing direct evidence for carbon-based magnetism and exploring candidate materials with promising practical applications in organic spintronics. , Diradical PAHs, with significant intramolecular ferromagnetic (FM) or antiferromagnetic (AFM) coupling between their radical centers within a reasonable distance, are suitable for fabricating organic magnetic materials. Experimental studies have demonstrated the interconversion between FM and AFM interactions by applying electric and magnetic fields and through the nondestructive rotation of flexible molecules . This unique property of diradical materials holds great potential for various applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organic diradicals offer the relative independence of the two unpaired electrons within one molecule. This characteristic allows for the control of electron spin–spin interaction through external stimuli such as temperature, pressure, and magnetic fields, rendering diradicals an ideal material system for spin-optical modulation (Figure c). Nevertheless, a challenge persists as many diradicals are nonluminescent or exhibit poor luminescence efficiency. , Additionally, they tend to form dimers or aggregates in the condensed state, posing difficulties in achieving spin-optical modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The first step in constructing a synthetic spin-1 chain using triangulene involved combining two triangulene molecules to form a triangulene dimer (TD), as illustrated in Figure (b). This was accomplished experimentally , and investigated theoretically ,,, in recent years. To understand the single-particle properties of the TD, we employ a p z orbital TB model, akin to previous studies. , One assumption in these TB models is that the hopping parameters between two sites depend solely on the distance between them.…”
mentioning
confidence: 99%